Impact of Reward and Loss Anticipation on Cognitive Control: An Event-Related Potential Study in Subjects With Schizophrenia and Healthy Controls. (January 2018) - Vignapiano, Annarita; Mucci, Armida; Merlotti, Eleonora; Giordano, Giulia Maria; Amodio, Antonella; Palumbo, Davide; Galderisi, Silvana
Introduction . Deficits of cognitive functions and motivation are core aspects of schizophrenia. The interaction of these deficits might contribute to impair the ability to flexibly adjust behavior in accordance with one's intentions and goals. Many studies have focused on the anterior N2 as a correlate of cognitive control based on motivational value. Aims . Given the key role of motivation impairment in schizophrenia as a predictor of functional outcome, we aimed to study the impact of reward- and avoidance-based motivation on cognitive control using N2. Method . Event-related potentials were recorded during the execution of the "Monetary Incentive Delay (MID)" task in 34 patients with schizophrenia (SCZ) stabilized on second-generation antipsychotics and 22 healthy controls (HC). Cognitive domains were assessed using the MATRICS Consensus Cognitive Battery. Negative symptom domains (Avolition/apathy and Expressive deficit), as well as positive and disorganization dimensions were also assessed in SCZ. Results . We did not observe any group difference in N2 amplitude or latency. In HC, N2 amplitude was significantly larger for anticipation of large loss with regard to all reward conditions and for all incentive versus neutral conditions. In SCZ, N2 amplitude did not discriminate between large loss and reward or between incentive and neutral conditions. N2 amplitude was not correlated with psychopathological dimensions or MCCB-assessed cognitive deficits in SCZ. Conclusion . Our data in HC are in line with the hypothesis that N2 amplitude reflects the impact of motivational salience on cognitive control. Our results in SCZ indicate a deficit in the discrimination of motivational salience to the service of cognitive control, independently of psychopathology and other cognitive deficits.